Design, fabrication & assembly of BEV propulsion battery sub-module - Ho, Samuel Xin Wei (2015)
The purpose of this report is to document the design, fabrication and assembly of the battery electric vehicle's propulsion battery sub-module. A background of the electric vehicle would be provided with a review on Li-ion cell characteristics. A large portion of work was done with SOLIDWORKS 2013 CAD and engineering drawings have been documented. The development of the sub-module design would be shown and the sequence of assembly is provided. Calculations include heat transfer and temperatures of pouch cells to aluminium multi-port extrusion, and also heat transfer from heat sinks, with some review of thermal .The work done to obtain temperature data from the pouch cells is included. A review of the standards and documented work done for crash test of traction batteries is included, followed by a drop test with SOLIDWORKS to simulate crash test of the propulsion battery sub-module.